PENDAMPINGAN PENGUATAN KARAKTER SISWA SEKOLAH MENENGAH TINGGI (SMA) AL-MUNIRI PAMEKASAN MELALUI PENGEMBANGAN BAHASA ASING (ARAB/INGGRIS) - Muhammad Hidayatullah; Muhammad Fattah Syamsuddin (Universitas Al-Amien Prenduan, 2022)
Speaking of education, the achievement of learning outcomes is absolutely necessary, because learning is not just transferring knowledge to children. More than that, learning should be able to empower students to be able to apply it in everyday life. In this institution, the achievement of language learning outcomes is quite optimal, because in reality students already have a basic language even though they still cannot apply their skills actively. But that does not mean this institution does not have potential, because students of this institution already have a basic language skills even though passively. Foreign language learning at various levels of educational institutions is so vibrant, ranging from education in elementary school to high school, why is that so? Because the learning of either a mother tongue or a foreign language is an obligation in formal education. So it's no wonder we get English lessons that in fact as a foreign language become lessons tested in the Final School Exam. This activity provides an achievement, namely an increase in language skills and the growth of love to learn the language. Students are becoming more familiar with language activities. Activities such as interactive dialogue and language competitions in Class Meeting events, managed to make students more familiar and familiarize themselves with the language. Because there is an increased interest in learning the language between before the empowerment event and after the empowerment event. Students have the motivation to learn a foreign language according to their individual interests. Students practice what they've learned when taking part in a race in a Class Meeting.